Actividades socioproductivas y economía familiar en la comunidad cañaveral ante las inundaciones del río Amazonas, Loreto 2025 - Vargas Machoa, Heidi Zaida (2025)
This descriptive and explanatory study, with a non-experimental, cross-sectional design, analyzes the adaptations and challenges of family economies and socio productive activities in the riverside community of Cañaveral, Loreto, in the face of the Amazon River flooding in 2025. A census sample of 25 families was used, applying structured surveys with closed-ended questions on a Likert scale. The instrument's reliability was validated using Cronbach's alpha coefficient, with a result of 0.785, indicating acceptable internal consistency. Data analysis included descriptive and inferential statistics, using the Shapiro-Wilk test to verify normality, and the Pearson correlation coefficient to explore relationships between variables. The results reveal that floods significantly affect family income, leading to loss of job opportunities, decreased income, and indebtedness. Adaptation strategies—such as economic diversification and work reorganization—are primarily reactive and lack institutional support. A widespread perception of state neglect is evident, highlighting the need for timely assistance and preventive training. The study concludes that there is a direct and significant relationship between the family economy and socio-productive activities during flood events, reflecting a structural interdependence between both dimensions and an increase in vulnerability.